Life cycle assessment model assisted by informatic tools, as support of the ecodesign teaching strategies at university level. (2019)
Eco-design is an innovation methodology with the objective of decreasing environmental impacts in the product life cycle. The best-known ecodesignmethodology is life-cycle assessment (LCA). This document presents the design and evaluation of LCA models aided by informatic tools as eco-design teaching support in a Colombian university. Eco-design teaching diagnosis, improvement scenarios and strategies were defined by triangulation of data from mixed research and the testing of LCA models .The active participation of the academic community is the way to promote ecodesign teaching and its contribution to sustainable development.